Low-level mosaic trisomy 2 at amniocentesis in a pregnancy associated with positive NIPT and CVS results for trisomy 2, maternal uniparental disomy 2, perinatal progressive decrease of the aneuploid cell line, cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, intrauterine growth restriction and a favorable fetal outcome - Chih-Ping Chen; Fang-Tzu Wu; Schu-Rern Chern; Peih-Shan Wu; Yen-Ting Pan; Chen-Chi Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2023)
Objective: We present low-level mosaic trisomy 2 at amniocentesis in a pregnancy associated with positive non-invasive prenatal testing (NIPT) and chorionic villus sampling (CVS) results for trisomy 2, maternal uniparental disomy (UPD) 2, perinatal progressive decrease of the aneuploid cell line, cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, intrauterine growth restriction (IUGR) and a favorable fetal outcome. Case Report: A 35-year-old, primigravid woman underwent amniocentesis at 16 weeks of gestation because both NIPT at 9 weeks of gestation and CVS at 11 weeks of gestation revealed trisomy 2. This pregnancy was conceived by in vitro fertilization (IVF) and embryo transfer (ET). Amniocentesis revealed a karyotype of 47,XY,+2[11]/46,XY[19]. Prenatal ultrasound findings were normal. She was referred to the hospital for genetic counseling at 20 weeks of gestation, and repeat amniocentesis performed at 24 weeks of gestation revealed a karyotype of 46,XY (22/22 colonies). The parental karyotypes were normal. Quantitative fluorescent polymerase chain reaction (QF-PCR) analysis on the DNA extracted from uncultured amniocytes and parental bloods revealed maternal uniparental heterodisomy of chromosome 2. Simultaneous molecular cytogenetic analysis on uncultured amniocytes showed the results of arr 2p25.3q37.3 × 2.4 with a log2 ratio = 0.26, consistent with 40% mosaicism for trisomy 2 by array comparative genomic hybridization (aCGH), and 28% (28/100 cells) mosaicism for trisomy 2 by interphase fluorescence in situ hybridization (FISH). Despite IUGR on fetal ultrasound, the woman was advised to continue the pregnancy, and a 2252-g phenotypically normal male baby was delivered at 38 weeks of gestation. The karyotypes of cord blood, umbilical cord and placenta were 46,XY (40/40 colonies), 46,XY (40/40 colonies) and 47,XY,+2[9]/46,XY[31], respectively. QF-PCR analysis on cord blood, umbilical cord and placenta confirmed uniparental heterodisomy of chromosome 2 in the cord blood and umbilical cord, and maternal origin of trisomy 2 in the placenta. FISH analysis on buccal mucosal cells at age 1.5 months revealed 8.7% (9/104 cells) mosaicism for trisomy 2. When follow-up at age four months, the neonate manifested a normal phenotype except intermittent hypoventilation. Molecular analysis of the PHOX2B gene revealed a normal result. When follow-up at age one year, he manifested normal development. Conclusion: Mosaic trisomy 2 at prenatal diagnosis should alert the possibility of UPD 2 and include a UPD 2 testing. Low-level mosaic trisomy 2 at amniocentesis can be associated with perinatal progressive decrease of the aneuploid cell line and a favorable fetal outcome.